Personality Predicts Health Declines Through Stressful Life Events During Late Mid-Life - Iacovino, Juliette M. (J Pers, 2015)
Personality predicts the occurrence of dependent stressful life events (SLE; i.e., events reliant, at least in part, on an individual's behavior). This process, termed stress generation, contributes to psychiatric outcomes, but its role in physical health is unknown. Data were included from 998 participants (aged 55–64) in the St. Louis Personality and Aging Network (SPAN) study. Assessments occurred every 6 months for 18 months. Neuroticism, impulsivity, and agreeableness were measured with the Revised NEO Personality Inventory. Dependent (e.g., divorce) and independent (e.g., family death) SLE occurring within 6 months following baseline were assessed with the List of Threatening Experiences and confirmed by interviews. Health problems occurring within a year after SLE were the outcome. Analyses examined whether neuroticism, impulsivity, and agreeableness indirectly predict the onset of new health problems through exposure to dependent SLE. Each personality trait was associated with dependent, but not independent, SLE. Only dependent SLE predicted new health problems. Each personality trait indirectly predicted the onset of new health problems through dependent SLE. Findings suggest that personality-driven stress generation influences physical health during late mid-life. Addressing personality in interventions may reduce the occurrence of SLE, in turn decreasing health risks.